Adaptasi Teknologi Untuk Mendukung Penguatan Kemampuan Literasi dan Numerasi Siswa Melalui Aplikasi AKM-Kelas Berbasis Desktop dan Android - Rafika Sari; Ajif Yunizar Pratama Yusuf; Khairunnisa Fadhilla Ramdhania; Muhammad Ganang Martyana; Illa Nur’aini; Syifa Rahmadhani; Renilda Filiandini; Reghita Suryani Putri (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The Minimum Competency Assessment (AKM) is an assessment of the basic competencies that all students need in order to be able to develop their own capacity and participate positively in society. The aim of AKM is to measure competency at the individual student level, which is expected for all students to reach a proficient or proficient level of competence. The minimum competency assessment since 2021 has been carried out online using the AKM-Kelas application provided by the Pusmenjar Kemdikbud. The challenge that later arises in implementing this is the ability of the school community to operate the application, apart from facilities and infrastructure, some schools do not yet have computer laboratory facilities. Based on this, the Kampus Mengajar (KM) program from the Merdeka Belajar Kampus Merdeka (MBKM) will work together to socialize and assist in using the AKM-Class application. In line with this, the participants in the Kampus Mengajar Batch 4 (KM-4) program at SDN 02 Jatireja designed a mentoring program for using the AKM-Kelas application in collaboration with the community service program (Pengabdian kepada Masyarakat - PkM) from Informatics lecturers at Bhayangkara University Jakarta Raya. Through this mentoring program, teachers and grade 5 elementary school students are the main targets as training participants. The main focus of this training is how to install desktop-based applications for teachers as proctors and install Android-based applications for students as AKM participants. This training program is carried out in stages over three consecutive months. The results of this training show an increase in competence that must be owned by teachers and students in the aspects of: AKM knowledge, literacy, numeracy.